Listeria dynamics in a laboratory-scale food chain of mealworm larvae (Tenebrio molitor) intended for human consumption. (August 2020) - Belleggia, Luca; Milanović, Vesna; Cardinali, Federica; Garofalo, Cristiana; Pasquini, Marina; Tavoletti, Stefano; Riolo, Paola; Ruschioni, Sara; Isidoro, Nunzio; Clementi, Francesca; Ntoumos, Athanasios; Aquilanti, Lucia; et al.
Abstract: The aim of the present study was to investigate Listeria innocua (used as a surrogate for Listeria monocytogenes ) dynamics in a laboratory-scale food chain of mealworm ( Tenebrio molitor ) larvae. To this end, a rearing substrate consisting of organic wheat middlings was spiked with L. innocua cells at three different contamination levels, namely 1, 5 and 7 Log colony-forming units (cfu) per gram. The dynamics of L. innocua were evaluated in larvae and frass samples collected during a 7-day rearing period. The effect of washing on the L. innocua load in the larvae at the end of the rearing period was assessed. Subsequently, the ability of four food treatment technologies (boiling, oven cooking, deep-frying, and freeze-drying) to kill L. innocua cells in the unwashed larvae was also evaluated. The overall results suggested that once L. innocua becomes established in the rearing environment, even at low levels, it may multiply in both the rearing substrate and the gut of larvae, representing a threat for the health of consumers. Regarding the processing of larvae, washing had no effect on the load of the test microorganism, whereas, as expected, the three heat-based food treatments (boiling, oven cooking, and deep frying) effectively killed all the Listeria cells carried by the larvae. Finally, frass generated by insects during rearing proved to be a potential source of environmental and food Listeria spp. contamination when not properly managed and disposed. Highlights: Listeria dynamics in a laboratory-scale food chain of mealworm larvae were studied. The results showed that Listeria was able to grow in the insect gut. Accumulation of viable Listeria cells in the insect frass was observed. Washing of larvae had no effect on the load of Listeria . Heat-based treatments were effective to kill Listeria cells.